2015
DOI: 10.1038/nn.3918
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic routing of task-relevant signals for decision making in dorsolateral prefrontal cortex

Abstract: Neurons in the dorsolateral prefrontal cortex (DLPFC) encode a diverse array of sensory and mnemonic signals, but little is known about how this information is dynamically routed during decision making. We analyzed the neuronal activity in the DLPFC of monkeys performing a probabilistic reversal task where information about the probability and magnitude of reward was provided by the target color and numerical cues, respectively. The location of the target of a given color was randomized across trials, and ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
123
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(139 citation statements)
references
References 50 publications
15
123
1
Order By: Relevance
“…The observation that neuronal activity represented the cues at the time of feedback is distinct from the "chosen-value" representations previously observed throughout the PFC (Padoa-Schioppa, 2009Sul et al, 2010;Kennerley et al, 2011;Donahue and Lee, 2015). Specifically, all the cues in our experiment were associated with identical reward, so neural activity could differentiate the cues solely by their visual features.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…The observation that neuronal activity represented the cues at the time of feedback is distinct from the "chosen-value" representations previously observed throughout the PFC (Padoa-Schioppa, 2009Sul et al, 2010;Kennerley et al, 2011;Donahue and Lee, 2015). Specifically, all the cues in our experiment were associated with identical reward, so neural activity could differentiate the cues solely by their visual features.…”
Section: Discussioncontrasting
confidence: 54%
“…Note that information about the correct cue picture could be present before the appearance of the cue array because a single cue was designated correct for an entire block. Note also that significant information about outcome can be present before the feedback epoch because the prior trial's outcome was reflected in the outcome categories used here (Asaad and Eskandar, 2011; Donahue and Lee, 2015).…”
Section: Neuronal Representations At the Time Of Feedbackmentioning
confidence: 99%
“…Our results are in line with a theoretical proposal11 recently supported by human functional magnetic resonance imaging (fMRI) and rat inactivation studies4650 that OFC represents the state-space, and hence add electrophysiological single-cell and neuronal population evidence for such theoretical scenario. In contrast, previous work has shown that in other brain areas, like the dorsolateral prefrontal cortex in monkeys, both task-relevant and task-irrelevant information is encoded in value-based decision-making4751. In addition, we also embedded animals in an environment in which they had to ignore prior information.…”
Section: Discussionmentioning
confidence: 98%
“…4; Supplementary Figs 4 and 8) was the number of neurons that had the firing rate significantly modulated by each task-variable over the total number of neurons used in the analysis. We preferred employing a permutation to test for significance in the regressors against more traditional methods that assume that the residuals are Gaussian204751, because the residuals that we observed in our data were strongly non-Gaussian. Furthermore, permutation tests are in general more conservative (lower probability of type I errors).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation